Ordinance no. 26, §§ 3, 4, 6, 7, 8, 42, 45, & 46, GRANTS PASS, REVISED ORDINANCES OF THE CITY (Rogue River Courier Print 1894) (Approved 1889). - (:unkn) unknown (General Publisher, 1889)
Regulated the brandishing, possession, discharge, and concealed carry of firearms.
--
Keywords: BRANDISHING; POSSESSION; DISCHARGE; CARRY - CONCEALED